2007
DOI: 10.1002/adma.200602705
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature In Situ Large‐Strain Plasticity of Silicon Nanowires

Abstract: Elastic-plastic and fracture properties are key issues in characterizing materials' mechanical behavior, and they have been extensively studied for over a century for bulk structured materials. [1][2][3] Silicon is one of the most important and representative materials for these studies owing to its extremely important applications. [4,5] Silicon nanowires (NWs) are one of the most important nanostructures used for fabricating various electronic and optoelectronic nanodevices, [6,7] and they could be a buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
267
6
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(293 citation statements)
references
References 31 publications
18
267
6
2
Order By: Relevance
“…The brittle facture observed in all our experiments is in contrary to a recent report by Han et al, 2 where large-strain plasticity was observed for Si NWs with diameters smaller than 60 nm under tension in TEM. The authors found that the tensile plasticity was initiated by the emergence of a high density of dislocations followed by the development of a continuous disordered lattice by the emission of dislocations.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…The brittle facture observed in all our experiments is in contrary to a recent report by Han et al, 2 where large-strain plasticity was observed for Si NWs with diameters smaller than 60 nm under tension in TEM. The authors found that the tensile plasticity was initiated by the emergence of a high density of dislocations followed by the development of a continuous disordered lattice by the emission of dislocations.…”
contrasting
confidence: 99%
“…27 Available experimental results on Si NWs exhibit significant scatter including the following: (1) some reported a decrease in Young's modulus with decreasing size, 2,9,24,28 while others showed an opposite trend; 20,21 (2) the reported strength values of vapor-liquid-solid (VLS) grown Si NWs ranged from 500 MPa to 12 GPa; 3,28 (3) Han et al 2 observed pronounced plastic deformation of Si NWs by in situ TEM tensile tests at room temperature, while Gordon et al 21 reported linear elastic behavior followed by brittle fracture using AFM bending tests.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, dislocations are easily generated on close-packed planes where dislocations slip with low resistance. [34][35][36][37] So we examined the dislocations on close-packed planes along several directions in the obtained TEM micrographs. Away from the zone of indentation impression, there are not so many dislocations comparing with the obvious pile-up of dislocations around grain boundaries underneath indenter impressions.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, nanowires have good mechanical performance, such as flexibility, fatigue durability, and so forth. 30 So PZT nanowires should be a good candidate for the high output ICLNG. Here, we use the electrospinning method to make well aligned PZT nanowires as shown in Figure 3a.…”
mentioning
confidence: 99%